Chronic and acute seizure activity affects NKCC1 and KCC2 expression and alters GABA-induced inhibition in the adult and developing hippocampus - Gielissen, Katherine A. (My University, 2008)
Temporal lobe epilepsy is a relatively common nervous system disorder characterized by abnormal activity in the hippocampus, often caused by a decrease in GABA inhibition. GABAA receptors are Cl- ion channels whose effects are medicated by inward Cl- rectifying (excitatory) NKCC1 and outward Cl- rectifying (inhibitory) KCC2 cotransporters. The expression of these cotransporters is modified by both aberrant neural activity and "critical periods" in development. We hypothesized the hippocampi class V seizures would cause a permanent upregulation of NKCC1 and/or downregulation of KCC2. We also hypothesized rats with seizures during postnatal days 20-30 would cause long term dysfunction in hippocampal expression of these cotransporters. Western blotting results suggest that increased propensity for seizures is due to permanent changes in NKCC1 levels, which subsequently reduces GABAA-mediated inhibition. Furthermore, developing rats that experience a seizure at P25 display decreased KCC2 expression levels both 24 hours and 90 days after the event, with little change in NKCC1 expression?with similar physiological effects as in adults.
23 p.
Keywords: Neurology; Biochemistry